Use of the neutrophil-to-lymphocyte ratio as a component of a score to predict postoperative mortality after surgery for hip fracture in elderly subjects. (December 2016) - Forget, Patrice; Dillien, Philippe; Engel, Harald; Cornu, Olivier; Kock, Marc; Yombi, Jean
Abstract Background Hip fracture precedes death in 12–37 % of elderly people. Identification of high risk patients may contribute to target those in whom optimal management, resource allocation and trials efficiency are needed. The aim of this study is to evaluate a predictive score of mortality after hip fracture in older persons on the basis of the objective prognostic factors easily available: age, sex and neutrophil-to-lymphocyte ratio (NLR) and C-reactive protein (CRP). Patients and methods After the ethical committee approval, we analyzed our prospective database including 286 consecutive older patients (>64 years) with hip fracture. A score [range 0–4] was constructed, based on a previous analysis, combining age (1 point per decade above 74 years), sex (1 point for male gender) and NLR at postoperative day +5 (1 point if > 5). A receiver-operating curve (ROC) analysis was performed. Similar analyses were performed with CRP (1 point if > 7.65 mg/dL). Results In the 286 patients (male 31 %), the median age was 84 (65–102) years, and the mean NLR values were 6.47 ± 6.07. At 1 year, 82/286 patients died (28.7 %). In the 235 patients with complete data, significant differences in term of mortality risk are observed (P  < 0.001). Performance analysis shows an AUC of 0.72[95 % CI 0.65–0.79]. CRP performed less than NLR (AUC for CRP alone: 0.53[95 % CI 0.45–0.61], P  = 0.42, with a sensitivity of 58.5 % and a specificity of 57.1 % for a cut-off value of 7.65 mg/dL; and for NLR alone: 0.59 [95 % CI 0.51–0.66];P  = 0.02, with a sensitivity of 55 % and a specificity of 65 % for a cut-off value of 4.9). Conclusion A discrete 0–4 scoring systems based on age, sex and the NLR was shown to be predictive of mortality in elderly patients during the first postoperative year following surgery for hip fracture repair.